THE OPTIMIZATION OF NATURAL CATALYSTS IN OIL PRODUCTION FROM PLASTIC WASTE PYROLYSIS - Denni Afriadi; Fazrul Muhammad Yasin (Universitas Airlangga, 2023)
This study was conducted to determine the effect of the amount of catalyst on yield from the pyrolysis of Polypropylene (PP) type plastic waste and to determine the characteristics of plastic waste pyrolysis oil which includes the physical and chemical properties of pyrolysis oil. The physical properties tested include viscosity, fire point, flash point, pour point, density, and water content while the chemical properties are compounds contained in pyrolysis oil using Gas ChromatoChromatography -Massmetry (GCMS) and knowing its calorific value. The research was conducted on the type of High-Density Polyethylene (HDPE), namely Polypropylene (PP) which was hydrolyzed in a batch reactor using an incinerator where heating originated from outside using wood powder and LPG. The ratio of raw materials used is as much as 1 kg of plastic with a variation of zeolite catalyst 0.25; 0.5; 0.75; 1 in kg. The results showed that the more catalysts added, the more pyrolysis oil was produced. The results of measuring oil at LEMIGAS kinematic viscosity at 40oC are 1.556 cST, 42 oC fire point, PMCC 26 o C flash point, pour point -42 o C, density at 15 o C 0.7857 g / cm3, and water content is 507.54 ppm . While the hydrocarbon compounds produced are pentene, heptane, and cyclohexane which have flammable properties. The calorific value produced from this pyrolysis oil is 40.947 Mj / Kg. The maximum amount of plastic oil volume is obtained by using 1 kg of raw material with 1 kg of 955 ml zeolite catalyst.